The Macroeconomic Determinants of Commodity Prices - Borensztein, Eduardo (IMF Working Papers; Working Paper ;, 1994)
The 'traditional structural approach' to the determination of real commodity prices has relied exclusively on demand factors as the fundamentals that explain the behavior of commodity prices. This framework, however, has been unable to explain the marked and sustained weakness in commodity prices during the 1980s and 1990s. This paper extends that framework in two important directions: First, it incorporates commodity supply in the analysis, capturing the impact on prices of the sharp increase in commodity exports of developing countries during the debt crisis of the 1980s. Second, we take a broader view of 'world' demand that extends beyond the industrial countries and includes output developments in Eastern Europe and the former Soviet Union (FSU). The empirical results support these extensions, as both the fit of the model improves substantially and, more importantly, its ability to forecast increases markedly.